Unmasking the Devil: The Role of the Civil Court and Islamic Religious Authorities in the Battle Against Religious Extremism and Terrorism in Malaysia - Khairil Azmin Mokhtar (Constitutional Review, 2022)
This paper sets out to examine the role of the court and the Islamic religious authorities in fighting religious extremism and terrorism in Malaysia. The judiciary has obligations to protect the people, to guarantee freedom and to dispense justice. It is the constitutional duty of the Islamic religious authorities to preserve the religion, to safeguard the Muslim and to insulate the teachings of Islam in Malaysia. Under the federal constitutional framework of the country, civil court and federal government do not deal with religious matters because it comes under the jurisdiction of Syariah laws and Syariah court of the states. However, in order to combat religious extremism and terrorism under the pretext of Islam, the demarcation of constitutional power and jurisdiction between federal and state governments is obscured. The federal government which has exclusive legislative and executive powers over criminal matters, public order and security have to collaborate with the Islamic religious authorities of the states in encountering threats coming from religious extremists and terrorists’ groups. Although laws, policies, and agencies relating to internal security, public order and crime are under the jurisdiction of the federal government, the ideological, theological, and philosophical dimensions of religious extremism and terrorism have to be dealt with by the Islamic religious authorities of the states. The civil court on a few occasions faced with challenging tasks of upholding rights of those accused of religious terrorism while at the same time preserving public order, peace, and security of the country. This is a qualitative research which involves legal study and analysis of primary materials including constitutions, legislations, emergency ordinances and court cases, and secondary materials such as books, articles and expert opinions. The symbiosis of federal authorities especially the civil courts, with the Islamic religious authorities of the states is the focal point of this paper. To counter the terrorists’ threats and combat the spreading of the dangerous extremists’ ideologies the court and the Islamic religious authorities need to have mutual understanding and establish cooperation in achieving the common goal. Only then the fight against religious extremism and terrorism in Malaysia is sustainable and effective.